2018
DOI: 10.1080/2162402x.2018.1424675
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA evaluated by Next-Generation Sequencing is predictive of tumor response and prolonged clinical benefit with nivolumab in advanced non-small cell lung cancer

Abstract: Nivolumab is an anti-PD1 antibody, given in second-line or later treatment in advanced non-small cell lung cancer (NSCLC). The objective of this study was to describe the predictive value of circulating tumor DNA (ctDNA) on the efficacy of nivolumab in advanced NSCLC. We prospectively included all consecutive patients with advanced NSCLC treated with nivolumab in our Department between June 2015 and October 2016. Plasma samples were obtained before the first injection of nivolumab and at the first tumor evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
0
53
0
Order By: Relevance
“…We next investigated whether the early decrease in peripheral ctDNA could predict prolonged survival in response to immunotherapy, as reported in ICB‐treated cohorts with relatively large cohort sizes. [ 12,14,23 ] Surprisingly, even with a small sample size of nine patients (P10 was excluded) with baseline blood samples in our cohort, the substantial early decrease in ctDNA abundance (≥50% decrease at eight weeks) predicted prolonged progression‐free survival after ICB administration (Figure S6, Supporting Information, ** p = 0.003 and HR = 6.005 [0.879–41.010]). These observations strongly support the use of ICP‐based ctDNA sequencing to identify patients likely to have favorable outcomes following ICB treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated whether the early decrease in peripheral ctDNA could predict prolonged survival in response to immunotherapy, as reported in ICB‐treated cohorts with relatively large cohort sizes. [ 12,14,23 ] Surprisingly, even with a small sample size of nine patients (P10 was excluded) with baseline blood samples in our cohort, the substantial early decrease in ctDNA abundance (≥50% decrease at eight weeks) predicted prolonged progression‐free survival after ICB administration (Figure S6, Supporting Information, ** p = 0.003 and HR = 6.005 [0.879–41.010]). These observations strongly support the use of ICP‐based ctDNA sequencing to identify patients likely to have favorable outcomes following ICB treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The OAK and POPLAR trials, which evaluated the efficacy of atezolizumab, showed a relationship between PFS and TMB of plasma ctDNA with FoundationOne CDx [60,61]. Giroux Leprieur et al [62] also showed that TMB of ctDNA determined by an NCS gene panel approach can predict the efficacy of nivolumab in patients with advanced NSCLC. Patients with a ctDNA increase > 9% from baseline to the first tumor evaluation at 2 months had no longterm clinical benefit with nivolumab with a sensitivity of 71.4% and specificity of 100%.…”
Section: Future Perspectives On Circulating Tumor Dna Testing In Lungmentioning
confidence: 99%
“…Circulating tumour DNA (ctDNA) has shown to be a good predictive marker of ICIs efficacy. [17][18][19] However, no study has been dedicated so far to other circulating biomarkers such as ICIrelated proteins or circulating microRNA (miRNA). The presence of soluble PD-L1 (sPD-L1) has already been established in patients with NSCLC with a prognostic impact of sPD-L1 concentrations.…”
Section: Introductionmentioning
confidence: 99%